Crack Detection Using Unmanned Aerial Vehicle (UAV) Applications - Chua, Wee Rou; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2023)
Crack detection is the most significant factor in building maintenance while unmanned aerial vehicles (UAV) is a technology which uses wireless remote sensing technology to control flight equipment, to traverse and take pictures of construction sites or facilities, and to measure and collect key information then transmitted to processing terminals. The objectives of this study are to identify the crack present at exterior structure by using Unmanned Aerial Vehicle (UAV) and also explore the ability of UAV in the inspection field. The data collection taken by capture the photos of the Kuaters Kediaman Institute of Land and Survey (INSTUN), Tanjong Malim, Perak by using PIX4D application and the pictures were transferred to the laptop and Adobe Photoshop are used for editing process. There are total of 33 cracks are identified through this study and the result can be used when carry out maintenance work. Recommendations are given to improve the efficiency of this study in future by increasing the camera’s quality to a higher resolution camera, using algorithm in analysis and pair the UAV with laser scanner.